(untitled) (Makerere University Journal of Agricultural & Environmental Sciences, 2004)
Production of potato (Solanum tuberosum L) in the highlands of Eastern Africa is increasingly being threatened by devastating epidemics of late blight (Phytophthora infestans (Mont.) de Bary). Use of fungicide sprays is a feasible control strategy against this epidemic but appropriate spray intervals during crop growth have not been determined. An on-farm experiment was therefore, conducted to establish the appropriate spray interval for a contact (Dithane M45) fungicide in Uganda. Results showed that during the blight-favourable seasons yields were higher with 7-day spray interval than 14 and 21 day but economic analysis revealed that 2 and 3 sprays of Dithane M45 on tolerant and susceptible cultivars, respectively resulted into optimal yields. Overall, monitoring disease and then spraying (2 sprays) contained late blight severity to levels that yielded the most economic benefit.